Expectant mothers' social media emotional support-seeking behavior - Ofori, Philomina Pomaah; Henaku, Thomas; Asamoah, Vered (Intelektual Pustaka Media Utama, 2024)
In developing countries, the use of digital media for health information by expectant mothers is a relatively new phenomenon, in contrast to developed countries. This study explores whether emotional support and satisfaction are linked and how they affect the use of social media for healthcare information. A non-experimental survey design was employed in this study. Expectant mothers were surveyed in five hospitals in Ghana's capital from May to August 2022 using a questionnaire. After reviewing and cleaning the data, 580 usable responses were obtained. The collected data were analyzed using SmartPLS 4 structural equation modeling. The findings of the study indicate that expectant mothers' decision to adopt digital media for health information is influenced by emotional support on social media (ESPSM) and satisfaction with social media (SATSM). Furthermore, satisfaction with social media partially mediated the effect between ESPSM and social media health information usage (SMHIU). These findings highlight the importance of emotional support and satisfaction with social media platforms in promoting digital health information usage. In particular, emotional support plays a crucial role for women, especially during pregnancy. These discoveries provide valuable insights for healthcare professionals on how best to assist expectant mothers.